2022
DOI: 10.1155/2022/8469756
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Oxidative Stress Impairs Cortical Synapse Formation and GABA Homeostasis in Parvalbumin-Expressing Interneurons

Abstract: Neonatal brain injury is often caused by preterm birth. Brain development is vulnerable to increased environmental stress, including oxidative stress challenges. Due to a premature change of the fetal living environment from low oxygen in utero into postnatal high-oxygen room air conditions ex utero, the immature preterm brain is exposed to a relative hyperoxia, which can induce oxidative stress and impair neuronal cell development. To simulate the drastic increase of oxygen exposure in the immature brain, 5-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Oxidative stress, especially during the most sensitive and early stages of brain development, has an adverse impact on brain neurodevelopment [50] and is proposed as a common factor in neurodevelopmental disorders such as schizophrenia and autism [51]. Our study found an increase in DCFH and protein carbonylation, indicating oxidative stress in DI patients, without changes in antioxidant defenses.…”
Section: Discussionmentioning
confidence: 45%
“…Oxidative stress, especially during the most sensitive and early stages of brain development, has an adverse impact on brain neurodevelopment [50] and is proposed as a common factor in neurodevelopmental disorders such as schizophrenia and autism [51]. Our study found an increase in DCFH and protein carbonylation, indicating oxidative stress in DI patients, without changes in antioxidant defenses.…”
Section: Discussionmentioning
confidence: 45%
“…Preterm birth may cause brain injury because newborns are prone to environmental stress, producing an excess of ROS, primarily due to the exposure to high‐oxygen condition compared to fetal life, with a marked increase of arterial oxygen tension. Thus, the preterm brain is exposed to hyperoxia, which induces oxidative stress and impairs neuronal cell development 36 . In particular, lipid peroxidation with reactive ROS leads to MDA production that can be used as a marker of the endogenous peroxidation of polyunsaturated fatty acids 8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the preterm brain is exposed to hyperoxia, which induces oxidative stress and impairs neuronal cell development. 36 In particular, lipid peroxidation with reactive ROS leads to MDA production that can be used as a marker of the endogenous peroxidation of polyunsaturated fatty acids. 8,9 It is also known that the preterm newborn's immature enzymatic oxidative stress defense system is incompetent to neutralize the increased formation of reactive ROS.…”
Section: Sepsis Amentioning
confidence: 99%
“…The pathogenesis of AD is still not elucidated clearly but oxidative stress is one of the key hypotheses. Related studies showed that oxidative stress is a driving force for synapse dysfunction [ [56] , [57] , [58] ]. Withaferin A is a natural drug with neuroprotective effects, such as anti-inflammatory and antioxidation effects.…”
Section: Discussionmentioning
confidence: 99%